Nilai Pendidikan Karakter dalam Jejak Andi Maruddani Karaengta Bonto-Bonto - Nur Maulindah Umar; Andi Agussalim; Aswati Asri (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to describe the values of character education in the saga